Exploring the Feasibility of Direct-Dispersion Oleogels in Healthier Sausage Formulations - Niaz Mahmud; Md. Jannatul Ferdaus; Roberta Claro da Silva (Gels)
Oleogels developed through the direct-dispersion method offer an innovative, scalable, and efficient alternative to traditional fats in sausage production, providing a solution to health concerns associated with the high saturated fat content of conventional formulations. By closely mimicking the texture, stability, and mouthfeel of animal fats, these oleogels provide a novel approach to improving the nutritional profile of sausages while maintaining desirable sensory characteristics. This review critically evaluates cutting-edge research on oleogels, emphasizing innovations in their ability to enhance emulsion stability, increase cooking yield, reduce processing weight loss, and optimize fatty acid composition by reducing overall fat and saturated fat levels. Despite their potential, sausage formulations with oleogel still face challenges in achieving consistent sensory properties, texture, and oxidative stability, often failing to fully replicate the sensory qualities and shelf-life of animal fats. To push the boundaries of oleogel technology and meet the increasing demand for healthier, high-quality sausage products, we propose focused innovations in refining oil-to-gelator ratios, exploring a wider range of novel gelators, optimizing production methods, and developing cost-effective, scalable strategies. These advancements hold significant potential for revolutionizing the sausage industry by improving both the technological and nutritional qualities of oleogels.